Ancient Occasional Host Switching of Maternally Transmitted Bacterial Symbionts of Chemosynthetic Vesicomyid Clams. (23rd August 2017) - Ozawa, Genki; Shimamura, Shigeru; Takaki, Yoshihiro; Takishita, Kiyotaka; Ikuta, Tetsuro; Barry, James P.; Maruyama, Tadashi; Fujikura, Katsunori; Yoshida, Takao
Abstract: Vesicomyid clams in deep-sea chemosynthetic ecosystems harbor sulfur-oxidizing bacteria in their gill epithelial cells. These symbionts, which are vertically transmitted, are species-specific and thought to have cospeciated with their hosts. However, recent studies indicate incongruent phylogenies between some vesicomyid clams and their symbionts, suggesting that symbionts are horizontally transmitted. To more precisely understand the evolution of vesicomyid clams and their symbionts, we compared the evolution of vesicomyid clams and their symbionts through phylogenetic analyses using multi-gene data sets. Many clades in the phylogenetic trees of 13 host species ( Abyssogena mariana, Ab. phaseoliformis, Akebiconcha kawamurai, Calyptogena fausta, C. laubieri, C. magnifica, C. nautilei, C. pacifica, Isorropodon fossajaponicum, Phreagena kilmeri, Ph. okutanii, Ph. soyoae, and Pliocardia stearnsii ) and their symbionts were well resolved. Six of the 13 host-symbiont pairs ( C. fausta, C. magnifica, C. pacifica, Ph. kilmeri, Ph. okutanii, and Ph. soyoae, and their respective symbionts) showed topological congruence. However, the remaining seven pairs ( Ak. kawamurai, Ab mariana, Ab. phaseoliformis, C. laubieri, C. nautilei, I. fossajaponicum, and Pl. stearnsii and their corresponding symbionts) showed incongruent topologies, which were supported by the approximately unbiased and Bayes factor tests. Coevolution analyses indicated that six pairs cospeciated, whereas host switching events occurred in the remaining seven pairs. Markedly, multiple host switching events may have occurred in the lineages from the common ancestral symbiont of C. pacifica and C. fausta. Our phylogenetic and coevolution analyses provide additional evidence for host switching during the evolution of vesicomyids.